Hadron production in Au-Au collisions at RHIC - Braun-Munzinger, Peter; Stachel, Johanna (Arxiv, 2001)
We present an analysis of particle production yields measured in central Au-Au collisions at RHIC in the framework of the statistical thermal model. We demonstrate that the model extrapolated from previous analyses at SPS and AGS energy is in good agreement with the available experimental data at $\sqrt s=130$ GeV implying a high degree of chemical equilibration. Performing a $χ^2$ fit to the data, the range of thermal parameters at chemical freezeout is determined. At present, the best agreement of the model and the data is obtained with the baryon chemical potential $μ_B\simeq 46± 5$ MeV and temperature $T\simeq 174± 7$ MeV. More ratios, such as multistrange baryon to meson, would be required to further constrain the chemical freezeout conditions. Extrapolating thermal parameters to higher energy, the predictions of the model for particle production in Au-Au reactions at $\sqrt s=200$ GeV are also given.